Flexomagnetic noncollinear state with a plumb line shape spin configuration in edged two-dimensional magnetic CrI₃ - Qiu, Guotao (2024)
The flexomagnetic effect involves the coupling of inhomogeneous mechanical and magnetic excitations to generate exotic spin orders. The intrinsic edge stress associated with lifting of periodic degeneracy at surfaces or edges in nanostructures facilitates the flexocoupling effects. Here, we combine first-principles calculation and Maximum Information Coefficient (MIC) statistics to quantitatively reveal the impact of bending on the geometries, spin ordering state, and exchange interactions in chromium triiodide (CrI3) nanoribbons. Our results reveal a divergent magnetic ground state at small curvature but a plumb line shape noncollinear state at large curvatures. More importantly, our work establishes a gradient dependence of the exchange coupling on the locally asymmetric bending angles of the Cr-I-Cr hinge, governed by the coupling of the t2g and eg states of Cr. The superexchange gradient accompanied with the bending-induced inhomogeneous deformation sheds light on the evolution of magnetic ordering associated with asymmetric coordinating systems for sensors and spintronics.